The Effect Of Discrete-Point Task Towards Student Writing Ability - Akmal Rais; Widya Syafitri (Universitas Pahlawan Tuanku Tambusai, 2021)
This research was discover the effect of using Discrete-point task towards students’ writing ability. Most of student got difficulties to organize the generic structure of text. This research used experimental research. The researcher used a quasi- experimental design by using the pre-test pos-test control group deisgn. The population of this research was tenth grade of in SMK Cendana Padang Panjang. The sample was X TKJ.1 which was treated as experimental class and taught by using Discrete-point task and X TKJ.2. The researcher used total sampling technique because the population less than a hundred. From the result of the pre-test and post-test scores of the experimental class, it was found that the t-obtained (8.25) was higher than the t-table (1.960). Then, the calculation of post-test both classes: experimental and control classes was obtained the (3.557) was bigger than t table (1.67). For the third hypothsis, mean score of the experimental class is bigger than control class (77.44 68.5).